Mucosal schwann cell hamartoma of the gall bladder - Kanika Sharma; Anjan Kumar Dhua; Prabudh Goel; Vishesh Jain; Devendra Kumar Yadav; Prashant Ramteke (Wolters Kluwer Medknow Publications, 2021)
Mucosal Schwann cell hamartoma (M-SCH) of the intestinal mucosa is a rare entity and incidental finding in histological examination. Histological characteristics are Schwannonian cell proliferation in lamina propria with S100-positivity. M-SCH-like lesion in the gall bladder is even rarer and is a recently reported entity. We report this extremely rare lesion in a cholecystectomy specimen of a 4-year-old boy, which makes it the youngest patient to be having M-SCH-like lesion in the gall bladder.